Design and Development of Extracellular Matrix Protein‐Based Microcapsules as Tools for Bacteria Investigation. Issue 11 (16th January 2023) - Pashapour, Sadaf; Seneca, Senne; Schröter, Martin; Frischknecht, Friedrich; Platzman, Ilia; Spatz, Joachim
Abstract: The extracellular matrix (ECM) plays an immense role in the homeostasis of tissues and organs, can function as a barrier for infectious agents, but is also exploited by pathogens during infection. Therefore, the development of well‐defined 3D ECM models in the form of microcapsules to elucidate the interactions between ECM components and pathogens in confinement and study disease infectivity is important, albeit challenging. Current limitations are mainly attributed to the lack of biocompatible methods for the production of protein‐based microcapsules. Herein, hollow ECM‐based microcapsules from laminin‐111 or laminin‐111/collagen IV are generated to investigate the behavior of organisms within confined 3D extracellular matrices. Microcapsules are created using water‐in‐oil emulsion droplets stabilized by block copolymer surfactants as templates for the charge‐mediated attraction of laminin or laminin‐collagen proteins to the droplets' inner periphery, allowing for the formation of modular ECM‐based microcapsules with tunable biophysical and biochemical properties and organism encapsulation. The release of E. coli ‐laden ECM‐based protein microcapsules into a physiological environment revealed differences in the dynamic behavior of E. coli depending on the constitution of the surrounding ECM protein matrix. The developed ECM‐based protein microcapsules have the potential to be implemented in several biomedical applications, including the design of in vitro infection models. Abstract : Extracellular matrix (ECM) protein‐based microcapsules are established for the very first time using a modular droplet‐based microfluidic technology. They help shed light on different dynamic bacterial behaviors in confined 3D ECM mimics, laying a foundation for the development of more advanced in vitro infection models and the bottom‐up assembly of fully synthetic ECM microenvironments.